Gender Inclusive Curriculum in Engineering and Construction Management : Final Report. - Mills, Julie; Ayre, Mary; Gill, Judith (Australian Learning and Teaching Council (ALTC), 2012)
Final report from a project that aimed to produce resources to bring about sustainable change in the teaching and learning of engineering and construction management (E&CM): to increase the enrolment of women; to accommodate the increasingly diverse student body; and to improve retention and success of all students. Two significant publications were produced. The first is the book Gender inclusive engineering education which advocates gender inclusive curriculum strategies and provides practical examples of their application. The second, Guidelines for the design of inclusive engineering education programs, summarises key messages and practical strategies from the book. It also provides advice on benchmarking E&CM programs and faculties with regard to gender inclusivity. The guidelines were widely disseminated to E&CM academics in Australia and have been proposed for adoption as an approved reference for Engineers Australia and construction management accreditation procedures. A series of workshops provided a theoretical framework and showcased examples of gender inclusivity. A project website has been developed as an ongoing resource for academics to implement gender inclusive strategies. Recommendations for embedding gender inclusive curriculum practices in E&CM have been made. If enacted, these will contribute to changed practices that should improve the attraction and retention of women to E&CM education.